2022
DOI: 10.1002/app.52408
|View full text |Cite
|
Sign up to set email alerts
|

Transamidation‐based vitrimers from renewable sources

Abstract: Vitrimers are polymeric materials that behave as thermosets at room temperature but, when heated, they exhibit a plastic flow similar to thermoplastics, enabling their reprocessability. A series of new bio-based polyamide-polyamine vitrimers are synthetized starting from tris(2-aminoethyl)amine and epoxidized methyl oleate, a material that can be easily prepared from renewable resources obtainable both from natural products and waste. The incorporation of free amine groups in the network enables the transamida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 43 publications
0
8
1
Order By: Relevance
“…43 In contrast to these dissociative CANs, transamidation vitrimers prepared from renewable resources were recently reported and presumed to involve an exchange between an amide and a free amine promoted by a boric acid catalyst. 80 Mechanistic considerations were not discussed in this study but the exchange seemed to occur through an associative pathway, in opposition to the previously reported dissociative CANs proceeding through the imide formation.…”
Section: Introductioncontrasting
confidence: 71%
“…43 In contrast to these dissociative CANs, transamidation vitrimers prepared from renewable resources were recently reported and presumed to involve an exchange between an amide and a free amine promoted by a boric acid catalyst. 80 Mechanistic considerations were not discussed in this study but the exchange seemed to occur through an associative pathway, in opposition to the previously reported dissociative CANs proceeding through the imide formation.…”
Section: Introductioncontrasting
confidence: 71%
“…Luca Pettazzoni et al have reported vitrimer utilizing transamidation chemistry using biobased sources. 94 The researchers have utilized waste vegetable oil, sunflower oil, and so forth, which are rich in triglyceride to obtain oleioc acid. Epoxidized methyl oleate crosslinked with tris(2-aminoethyl)amine has been used to obtain polyamide-polyamine vitrimer.…”
Section: Boronic Ester Exchangementioning
confidence: 99%
“…30 In the transamidation self-healing mechanism, the reaction between amide linkages and free amines forms reversible amide adducts. 47 These adducts hence act as reversible crosslinks that can be broken and reformed, allowing the material to heal itself.…”
Section: Underlying Mechanismsmentioning
confidence: 99%